Предмет: Алгебра,
автор: MarGGoTV
довести, що 1) (а-8)(а+7)>(а+10)(а-11) 2) (а+6)(b+3)(c+2)>48√abc СРОЧНОО
Ответы
Автор ответа:
0
Решение
1) (а-8)(а+7) - (а+10)(а-11) = a² - a - 56 - a² + a + 110 = 54 > 0, значит
(а-8)(а+7) > (а+10)(а-11) Доказано
Аналогично решается
2) (а+6)(b+3)(c+2) - 48√abc =
1) (а-8)(а+7) - (а+10)(а-11) = a² - a - 56 - a² + a + 110 = 54 > 0, значит
(а-8)(а+7) > (а+10)(а-11) Доказано
Аналогично решается
2) (а+6)(b+3)(c+2) - 48√abc =
Похожие вопросы
Предмет: Английский язык,
автор: starikovakarolina831
Предмет: Қазақ тiлi,
автор: narajmukaseva
Предмет: Українська мова,
автор: gumyanchik1410
Предмет: Математика,
автор: iriska131279